Atypical Radiographic Presentation of Adenocarcinoma Lung (Bangladesh Journal of Medical Science, 2013)
Adenocarcinoma and squamous cell carcinoma are the most frequently diagnosed histological subtype of bronchogenic carcinomas. Though metastatic lesions in lung are common in both the varieties, cavity formation has been documented only with squamous cell type. Here we are going to report a case of pulmonary adenocarcinoma with multiple nodular metastases in both lungs which show central necrosis mimicking cavities. DOI: http://dx.doi.org/10.3329/bjms.v13i1.13037 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 70-72